2019
DOI: 10.1007/s10815-019-01459-0
|View full text |Cite
|
Sign up to set email alerts
|

Can follicular Emmprin and BMP 4 levels predict ICSI outcome?

Abstract: Purpose To evaluate the relationship of clinical pregnancy rates with bone morphogenetic proteins 2-4-7 (BMP 2, 4, 7), growth differentiation factor 9 (GDF 9), and Emmprin levels in follicular fluid of intracytoplasmic sperm injection patients. Methods Follicular fluid of 77 patients who underwent ICSI procedure was collected during the oocyte retrieval procedure. And follicular fluid levels of BMP 2, BMP 4, BMP 7, GDF 9, and Emmprin (Basigin) were measured and compared for clinical pregnancy rates. Results Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, BSG gene expression has been shown to cause mouse infertility with an abnormal fertilization process and impaired embryo implantation [ 10 ]. Moreover, it was found that the concentration of BSG protein in the follicular fluid is associated with clinical pregnancy rate in patients undergoing in vitro fertilization, more specifically intracytoplasmic sperm injection (ICSI); at lower concentrations of this protein, the clinical pregnancy rate was higher, therefore, this protein was proposed as a marker for predicting ICSI outcomes [ 41 ]. Taking these functions into account, SARS-CoV-2 might disturb the female reproductive functions through regulating the ACE2 and BSG gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BSG gene expression has been shown to cause mouse infertility with an abnormal fertilization process and impaired embryo implantation [ 10 ]. Moreover, it was found that the concentration of BSG protein in the follicular fluid is associated with clinical pregnancy rate in patients undergoing in vitro fertilization, more specifically intracytoplasmic sperm injection (ICSI); at lower concentrations of this protein, the clinical pregnancy rate was higher, therefore, this protein was proposed as a marker for predicting ICSI outcomes [ 41 ]. Taking these functions into account, SARS-CoV-2 might disturb the female reproductive functions through regulating the ACE2 and BSG gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of these proteins was due to their ability to induce bone and cartilage formation. BMPs are now thought of as a group of axial morphogenic messengers that harmonize tissue architecture throughout the body (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%